Children Exposed to Marital Violence: Theory, Research, and Applied Issues. 1998
DOI: 10.1037/10257-009
|View full text |Cite
|
Sign up to set email alerts
|

Parenting behaviors and beliefs of battered women.

Abstract: now well recognized that children living in families characterized marital violence are victimized in a variety of ways. They are terrorized by hearing and seeing violent marital interactions. They are often subjected to a range of forms of psychological maltreatment, including being degraded, rejected, denied emotional responsiveness, and isolated from others (Geffner, 1996). Furthermore, they may be the recipients of physical abuse themselves: Studies are finding an overlap between marital violence and child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
95
0
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 40 publications
1
95
0
7
Order By: Relevance
“…There are few studies that have examined contributing factors to poor health in violence-exposed children, and even fewer that have looked specifically at preschool children (see Attala and Summers 1999;Graham-Bermann and Seng 2005 for some that do). Yet, this age group is especially important to study as developmentally, preschool-age children are vulnerable to considerable impairment across the lifespan (e.g., Fantuzzo et al 1991;Holden et al 1998;Yates et al 2003). Furthermore, the psychological impairments associated with early childhood exposure to violence have been studied extensively (see Howell and Graham-Bermann 2011 for a review), while the physical health consequences of exposure to violence are relatively neglected as an outcome.…”
Section: Associations Between Poor Physical Health and Exposure To VImentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies that have examined contributing factors to poor health in violence-exposed children, and even fewer that have looked specifically at preschool children (see Attala and Summers 1999;Graham-Bermann and Seng 2005 for some that do). Yet, this age group is especially important to study as developmentally, preschool-age children are vulnerable to considerable impairment across the lifespan (e.g., Fantuzzo et al 1991;Holden et al 1998;Yates et al 2003). Furthermore, the psychological impairments associated with early childhood exposure to violence have been studied extensively (see Howell and Graham-Bermann 2011 for a review), while the physical health consequences of exposure to violence are relatively neglected as an outcome.…”
Section: Associations Between Poor Physical Health and Exposure To VImentioning
confidence: 99%
“…Instead, they vary depending on the intensity and type of violence and the child's vulnerability at certain points in development (Howell et al 2010;Margolin 2005). More specifically, research on IPV has consistently shown that the effects of violence are most substantial when the child is of preschool age (Fantuzzo et al 1991;Holden et al 1998;Yates et al 2003) and when the violence is committed by or against trusted adults (Gunnar and Donzella 2002;Little and Kantor 2002). These trusted adults, however, may be related to the child and mother in a number of ways, as the research has suggested that behavioral disruptions in children do not differ when the perpetrator is the child's biological father as compared to a stepfather or other male caregiver (Israel and Stover 2009).…”
mentioning
confidence: 99%
“…In a meta-analytic review of 68 studies on marital conflict, Erel and Burman (1995) found support for this "spillover hypothesis." Studies of the effects of DV on women's parenting suggest a positive relationship between DV and power-assertive parenting as well as DV and control tactics (Margolin & Gordis, 2003), inconsistent discipline (Holden, Stein, Ritchie, Harris, & Jouriles, 1998), and greater parenting stress (Levendosky & Graham-Bermann, 1998).…”
Section: Effects Of Domestic Violencementioning
confidence: 99%
“…A deficit model of parenting in battered women has been reported based on findings that some victims of domestic violence are more likely to be aggressive toward their children (Straus & Gelles, 1990), display less warmth in their parent-child interactions (McCloskey, Figueredo, & Koss, 1995), and be less consistent in their parenting efforts than are nonabused mothers (Holden, Stein, Ritchie, Harris, & Jouriles, 1998). It is not surprising that parent-child relationships can be deeply affected when battered mothers are forced to cope with their own physical injuries and emotional reactions to their victimization (Wolfe et al, 1985).…”
Section: Parenting In the Context Of Domestic Violencementioning
confidence: 99%
“…Battered mothers also may be fearful for their children's safety and upon the realization that they are unable to protect their children from exposure to domestic violence, women's responses can include anxiety, helplessness, and frustration (Osofsky & Fenichel, 1994). In at least one study, battered women were reported to modify their parenting styles when their abusive partners were present and did so with the goal of minimizing the likelihood of violence by the batterers (Holden et al, 1998).…”
Section: Parenting In the Context Of Domestic Violencementioning
confidence: 99%